2020
DOI: 10.1371/journal.pone.0235562
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex-adjusted incidence and yearly prevalence of multiple sclerosis (MS) in Mazandaran province, Iran: An 11-years study

Abstract: Introduction The incidence rate of MS is a valuable indicator of the recent changes in the risk of this disease, and it is widely implicated for health planning purposes. Objectives This study aims to determine the MS incidence over the past eleven years in Mazandaran province and to compare it with the other parts of Iran and the world. Materials and methods This retrospective study is conducted in Mazandaran province by using registered data in the files of the patients with their consent. The yearly crude i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Stress inflicted on human society due to disasters in various studies related to different hazards as a risk factor in the occurrence or exacerbation of various diseases, especially chronic and noncommunicable diseases such as psychological disorders (PTSD, depression, etc. ), hypertension and diabetes has been revealed (51,52). These findings emphasize the importance of psychological support in disasters and preventive interventions to reduce the perceived stress of disasters (53).…”
Section: Discussionmentioning
confidence: 77%
“…Stress inflicted on human society due to disasters in various studies related to different hazards as a risk factor in the occurrence or exacerbation of various diseases, especially chronic and noncommunicable diseases such as psychological disorders (PTSD, depression, etc. ), hypertension and diabetes has been revealed (51,52). These findings emphasize the importance of psychological support in disasters and preventive interventions to reduce the perceived stress of disasters (53).…”
Section: Discussionmentioning
confidence: 77%
“…12 A retrospective study on the age incidence of multiple sclerosis by Cheraghmakani Et al, showed that the age group 60-64, the incidence of MS is 1.5 times higher than the baseline age group of 10-15 years. 13 Aging is associated with brain iron accumulation, these age-related increases in brain iron concentration are associated with the disruption of WM. While myocarditis post-COVID vaccines, tend to occur after the second dose, demyelinating disorders are mostly occurring after the first dose.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous ndings, the incidence of MS in Mazandaran province has increased in recent years, and the increase is observed in both genders and individuals with positive family history. Although the interaction between genetic and environmental factors has played a role in enhancing its incidence rate, environmental factors seem to play a more potent role (5)(6)(7). The present study aimed to determine the role of each factor and their effect size on the MS development in a case-control study.…”
Section: Introductionmentioning
confidence: 94%